The use of a scented face mask in pediatric patients may facilitate mask acceptance before anesthesia induction - Abukawa, Yukako; Takano, Koji; Hobo, Yuko; Hosaka, Erika; Kimura, Ayano; Suga, Yoshifumi; Katori, Nobuyuki; Tsubokawa, Tsunehisa (Frontiers in Medicine, 2023)
Background: Scented face masks are commonly used during the induction phase of anesthesia. The present study investigated whether the use of a scented mask improved mask acceptance before the slow induction of anesthesia in pediatric patients. Methods: This prospective, randomized controlled trial enrolled patients aged 2–10 years who were scheduled to undergo surgery under general anesthesia. Patients were randomly assigned to either of regular unscented (control group) or scented (experimental group) face masks before anesthesia induction with a parent. The primary outcome was the mask acceptance score, rated on a validated 4-point from 1 point (not afraid; easily accepts the mask) to 4 points (afraid of a mask; crying or struggling). The secondary outcome was heart rate assessed by pulse oximetry in the pediatric ward before transfer to the operating room (OR), at the entrance to the OR, at the patient notification of mask fitting by the anesthesiologist, and after mask fitting. Results: Seventy-seven patients were accessed for eligibility, with 67 enrolled in the study: 33 in the experimental group and 34 in the control group. Mask acceptance was significantly greater among patients aged 2–3 years in the experimental than in the control group (p < 0.05). Conclusions: The use of a scented mask can improve mask acceptance before anesthesia induction with a parental presence in pediatric patients aged 2–3 years.